Can the Salivary Microbiome Predict Cardiovascular Diseases? Lessons Learned From the Qatari Population - Murugesan, Selvasankar; Elanbari, Mohammed; Bangarusamy, Dhinoth Kumar; Terranegra, Annalisa; Al Khodor, Souhaila (Frontiers in Microbiology, 2021)
Background Many studies have linked dysbiosis of the gut microbiome to the development of cardiovascular diseases (CVD). However, studies assessing the association between the salivary microbiome and CVD risk on a large cohort remain sparse. This study aims to identify whether a predictive salivary microbiome signature is associated with a high risk of developing CVD in the Qatari population. Methods Saliva samples from 2974 Qatar Genome Project (QGP) participants were collected from Qatar Biobank (QBB). Based on the CVD score, subjects were classified into low-risk (LR<10) (n=2491), moderate-risk (MR=10-20) (n=320) and high-risk (HR>30) (n=163). To assess the salivary microbiome (SM) composition, 16S-rDNA libraries were sequenced and analyzed using QIIME-pipeline. Machine Learning (ML) strategies were used to identify SM-based predictors of CVD risk. Results Firmicutes and Bacteroidetes were the predominant phyla among all the subjects included. LefSe analysis revealed that Clostridiaceae and Capnocytophaga were the most significantly abundant genera in the LR group, while Lactobacillus and Rothia were significantly abundant in the HR group. ML-based prediction models revealed that Desulfobulbus, Prevotella, and Tissierellaceae were the common predictors of increased risk to CVD. Conclusions This study identified significant differences in the SM composition in HR and LR CVD subjects. This is the first study to apply ML-based prediction modeling using the SM to predict CVD in an Arab population. More studies are required to better understand the mechanisms of how those microbes contribute to CVD.